APPLICATION OF ADMINISTRATIVE SANCTIONS ON ENVIRONMENTAL MANAGEMENT IN BOGOR REGENCY - Dr. Asmak ul Hosnah, MH; Dr. Henny Suharyati, M.Si.; Eka Ardianto, SH., MH (Novateur Publications, 2023)
The maintenance of the ongoing function of the environment is in the interest of the people, thus demanding responsibility, openness and the role of community members, which can be channeled through individuals, environmental organizations, such as non-governmental organizations, indigenous peoples' groups and others, in order to maintain and increase the carrying capacity and accommodating capacity of the environment on which sustainable development depends. Therefore, the Indonesian environment must be managed with the principle of preserving harmonious, harmonious and balanced environmental functions to support sustainable development with an environmental perspective for improving the welfare and quality of life of present and future generations.
Keywords: Administrative Sanctions; Environmental Management